Elucidating the molecular docking and binding dynamics of aptamers with spike proteins across SARS-CoV-2 variants of concern - Quintela, Irwin A.; Vasse, Tyler; Jian, Dana; Harrington, Cameron; Sien, Wesley; Wu, Vivian C. H. (Frontiers in Microbiology, 2025)
DNA aptamers with high binding affinity against SARS-CoV-2 spike proteins have been selected and analyzed. To better understand the binding affinities between DNA aptamers and spike proteins (S-proteins) of relevant variants of concerns (VOCs), in silico and in vitro characterization are excellent approaches to implement. Here, we identified and generated DNA aptamer sequences targeting the S-protein of SARS-CoV-2 VOCs through systematic evolution of ligands by exponential enrichment (SELEX). In silico, prediction of aptamer binding was conducted, followed by a step-by-step workflow for secondary and tertiary aptamer structures determination, modeling, and molecular docking to target S-protein. The in silico strategy was limited to only providing predictions of possible outcomes based on scores, and ranking was complemented by characterization and analysis of identified DNA aptamers using a direct enzyme-linked oligonucleotides assay (ELONA), which showed dissociation constants (Kd) within the 32 nM–193 nM range across the three significant VOCs. These three highly specific VOCs aptamers (Alpha Apt, Delta Apt, and Omicron Apt) can be further studied as potential candidates for both diagnostic and therapeutic applications.